The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19074355
|View full text |Cite
|
Sign up to set email alerts
|

What We Know and What Remains to Be Explored about LGBTQ Parent Families in Israel: A Sociocultural Perspective

Abstract: This paper reviews research on gay and lesbian parent families in Israel through cultural lenses while recognizing the diversity of these families. The major aims of the review are: (1) to provide an overview of the situation of LGBTQ parent families in Israel, as well as of the sociocultural background of the Israeli context and its effects on sexual minorities and LGBTQ parent families; and (2) to identify the limitations and lacunas in the existing research and shed light on what remains to be explored. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Moreover, it has been suggested that the sense of victory on succeeding to become gay fathers in the Israeli pronatalist sociocultural context, which highly cherishes childrearing and yet imposes restrictions on gay men who want to become fathers, is another possible contributor to the higher levels of life satisfaction and growth found among Israeli gay fathers [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been suggested that the sense of victory on succeeding to become gay fathers in the Israeli pronatalist sociocultural context, which highly cherishes childrearing and yet imposes restrictions on gay men who want to become fathers, is another possible contributor to the higher levels of life satisfaction and growth found among Israeli gay fathers [22].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have usually been explained in the context of the Israeli pronatalist and familistic sociocultural atmosphere. In this context, realizing fatherhood desires, especially after contending with the numerous hurdles restricting gay men's access to fatherhood, could lead to a sense of victory and elevated levels of of both hedonic and eudaimonic well-being [22,23]. Similarly, as parenthood is considered a primary path to social acceptance and inclusion in Israel's familistic society, it has been suggested that the transition to fatherhood among gay men may tap into a stronger sense of social acceptance and belongingness that could also explain the elevated levels of well-being [24].…”
Section: Introductionmentioning
confidence: 99%
“…The examined research was carried out using primarily Western and Westernized samples, which limits the extent to which the findings can be generalized to families in other geographic regions [ 106 , 107 ]. In light of the rapid growth in international fertility procedures worldwide [ 108 ], it is important that future research include families from more diverse geographic locations.…”
Section: Future Directions and Clinical Implicationsmentioning
confidence: 99%
“…Common explanations for these differences emphasize the deliberate, intentional, and planned nature of sexual minority parenthood, as well as personal psychological resources associated with the ability to contend with the financial and bureaucratic challenges of pursuing parenthood as a sexual minority individual (Shenkman & Shmotkin, 2014;Shenkman et al, 2022c). To date, no research has investigated the specific role played by parents' positivity (i.e., the tendency to view life with a positive outlook) in determining better mental health outcomes among sexual minority parents, relative to heterosexual parents.…”
Section: Introductionmentioning
confidence: 99%